Cost-Effectiveness Analysis of Sunitinib versus Interferon-Alfa for First-Line Treatment of Advanced and/or Metastatic Renal Cell Carcinoma in Singapore. (11th March 2019) - Pruis, Sil-ling; Aziz, Mohamed Ismail Abdul; Pearce, Fiona; Tan, Min Han; Wu, David Bin-Chia; Ng, Kwong
Abstract: Objectives: This study was conducted to evaluate the cost-effectiveness of sunitinib versus interferon-alfa for the treatment of advanced and/or metastatic renal cell carcinoma (RCC) in Singapore. Methods: A partitioned survival model with three health states (progression-free, progressive disease, and death) was developed from a healthcare payer perspective over a 10-year time horizon. Survival curves from the pivotal trial of sunitinib versus interferon-alfa were extrapolated beyond the trial period to estimate the underlying progression-free survival and overall survival parametric distributions. Health state utilities were derived from the literature and direct costs were sourced from local public healthcare institutions. The sunitinib dose in the model reflected local prescribing practices whereby a combination of 50 mg (28 percent) and 37.5 mg (72 percent) strengths are used. Results: The base-case analysis comparing sunitinib versus interferon-alfa resulted in an incremental cost effectiveness ratio (ICER) of SGD191, 061 (USD139, 757) per quality-adjusted life-year gained. Sensitivity analysis demonstrated that the ICER was most sensitive to variations in the utility value assumed for the progression-free health state and the price of sunitinib. Conclusions: In the absence of any price reduction, sunitinib had an exceedingly high ICER and was not considered a cost-effective use of healthcare resources in Singapore's context for the first-line treatment of advanced RCC. The findings from our evaluation will be useful to inform local healthcare decision making and resource allocations for tyrosine kinase inhibitors when appraised alongside comparative clinical effectiveness data and payer affordability considerations.